Utility of prospective step sections in diagnostic skin histopathology for small biopsies - G Kattel; AK Sinha; S Agrawal (Association of Clinical Pathologists of Nepal, 2014)
Background: Small skin biopsies have a cosmetic advantage and prospective step sections could potentially improve turnaround time without compromising diagnostic information. The study aimed to examine the use of prospective step sections of small skin biopsies and its effect on histopathological diagnosis and turnaround time. Materials and Methods: This was a hospital based cross-sectional study at Department of Pathology and Department of Dermatology, BPKIHS from June 2011- June 2012. Diagnoses /comment on three levels of prospectively taken 3mm biopsies were compared with those of 5mm biopsies taken from the same/similar lesion from 100 patients. Additional sections from 5mm biopsies were taken retrospectively. Percentage, proportion, mean, standard deviation, diagnostic sensitivity, kappa statistics and paired sample t- test were used as statistical tools. Results: Of 100 cases, 80 were diagnosed using 5mm biopsies while 73 were diagnosed using 3mm biopsies. On additional step sections of 3mm biopsies, 3 more cases were diagnosed. When compared with 5mm biopsies, the sensitivity of the 3mm biopsy rose from 90% to 93.8% after additional sections while the measure of agreement rose from 0.751 to 0.826.Mean turnaround time for prospectively sectioned 3mm biopsies was 2.56 days and that of retrospectively sectioned 5 mm biopsies was 4.64 days with their difference being statistically significant. Conclusion: A statistically significant decrease in turnaround time and an increase in sensitivity and agreement after step sections elucidates the utility of prospective step sectioned 3 mm biopsies in diagnostic skin histopathology. DOI: http://dx.doi.org/10.3126/jpn.v4i7.10298 Journal of Pathology of Nepal (2014) Vol. 4, 552-559